2022
DOI: 10.3389/fendo.2022.915449
|View full text |Cite
|
Sign up to set email alerts
|

Association of Plasma Neurofilament Light Chain With Glycaemic Control and Insulin Resistance in Middle-Aged Adults

Abstract: AimsThis study aimed to determine the association of plasma neurofilament light (NfL), a marker of neurodegeneration, with diabetes status and glycaemic parameters in people with normal glycaemia (NG), pre-diabetes (PD) and type 2 diabetes (T2D).MethodsClinical and descriptive data for the diagnostic groups, NG (n=30), PD (n=48) and T2D (n=29), aged between 40 and 75 years were included in this cross-sectional analysis. Plasma NfL levels were analyzed using the ultra-sensitive single-molecule array (Simoa) pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…NfL levels might be impacted by medical comorbidities that are common among elders, complicating its utility as a biomarker. Although multiple sclerosis, neurodegenerative dementia, stroke, amyotrophic lateral sclerosis (Khalil et al, 2018), orthostatic hypotension (Park et al, 2021), hearing disorder (Park et al, 2016;Han et al, 2018), depression and anxiety disorders (Tauil et al, 2021), diabetes (Thota et al, 2022), psoriasis (Nowowiejska et al, 2022), transient ischemic attack (TIA;De Marchis et al, 2018) and sleep disorder (Jennum et al, 2017;Lysen et al, 2020;Targa et al, 2021) might impact NfL levels, we still found consistent results after adjusting for medical comorbidities. CSF NfL can purposefully play the role of a future candidate for CSF biomarkers when cognitive disorder risk is estimated among patients with PD (Hoops et al, 2009).…”
Section: Discussionsupporting
confidence: 62%
“…NfL levels might be impacted by medical comorbidities that are common among elders, complicating its utility as a biomarker. Although multiple sclerosis, neurodegenerative dementia, stroke, amyotrophic lateral sclerosis (Khalil et al, 2018), orthostatic hypotension (Park et al, 2021), hearing disorder (Park et al, 2016;Han et al, 2018), depression and anxiety disorders (Tauil et al, 2021), diabetes (Thota et al, 2022), psoriasis (Nowowiejska et al, 2022), transient ischemic attack (TIA;De Marchis et al, 2018) and sleep disorder (Jennum et al, 2017;Lysen et al, 2020;Targa et al, 2021) might impact NfL levels, we still found consistent results after adjusting for medical comorbidities. CSF NfL can purposefully play the role of a future candidate for CSF biomarkers when cognitive disorder risk is estimated among patients with PD (Hoops et al, 2009).…”
Section: Discussionsupporting
confidence: 62%
“…It is not completely clear if comorbidities may impact plasma NfL levels. There is some evidence that plasma NfL levels could be influenced by body mass index (BMI) [ 58 , 59 ], renal function [ 60 ], and diabetes [ 61 ]. However, as previously showed by Koini et al [ 62 ], the impact that comorbidities could have on plasma NfL levels is influenced by the age of the individual.…”
Section: Discussionmentioning
confidence: 99%
“…NfL levels were lower in Aβ− participants. As plasma NfL levels are associated with aging and diabetes mellitus (DM), 35 older age and higher prevalence of DM in our Aβ− participants may have led to these results. In the current study, NfL levels were higher in patients with DM, but p‐tau181, Aβ42, and Aβ40 were not (Table S6).…”
Section: Discussionmentioning
confidence: 65%